Development and Psychometric Properties of a Theory-Guided Prescription Stimulant Misuse Questionnaire for College Students. (23rd April 2013) - Bavarian, Niloofar; Flay, Brian R.; Ketcham, Patricia L.; Smit, Ellen
<x xml:space="preserve">Abstract</x> A theory-guided instrument for examining prescription stimulant misuse in the college population was developed and its psychometric properties were evaluated from 2011 to 2012 at one Pacific Northwest (United States) university. Study methods included instrument development, assessment by five health and measurement professionals, group interviews with six college students, a test-retest pilot study, and a paper-based, in-classroom, campus study using one-stage cluster sampling (N = 520 students, 20 classrooms, eligible student response rate = 96.30%). The instrument demonstrated reliability (i.e., internal consistency and stability) and validity (i.e., face, content, and predictive). Limitations and implications are discussed.